Interfaces and Nanostructures of Functional Oxide Octahedral Framework Structures - Sandiumenge, Felip; Bagués, Núria; Santiso, José (Frontiers in Materials, 2014)
In the past decade, the rich physics exhibited by solid interfaces combining octahedral framework structures of transition metal oxides has fascinated the materials science community. However, the behavior of these materials still elude the current understanding of classical semiconductor and metal epitaxy. The reason for that is rooted in the surprising versatility of linked coordination units to adapt to a dissimilar substrate and the strong sensitivity of correlated oxides to external perturbations. The confluence of atomic control in oxide thin film epitaxy, state of the art high spatial resolution characterization techniques, and electronic structure computations, has allowed in recent years to obtain first insights on the underlying microscopic mechanisms governing the epitaxy of these fascinating materials. Here, we shortly review these mechanisms and highlight their potential in the design of novel nanostructures with enhanced functionalities.